2021
DOI: 10.1002/cam4.4267
|View full text |Cite
|
Sign up to set email alerts
|

Positive electrostatic therapy of metastatic tumors: selective induction of apoptosis in cancer cells by pure charges

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 57 publications
(60 reference statements)
1
12
0
Order By: Relevance
“…We observed that 4T1 TNBC cells undergo apoptosis when treated with iEFs in vitro. This finding is notable, especially in the context of bioelectricity, as other methods of applying electrical current or fields, such as tumor treating fields 47 (TTFs) and positive electrostatic charge therapy 48,49 (PECT), have also reported selective apoptosis of cancer cells. In addition, a recent study showed that TTFs enhance anti-tumor immune activation in a murine glioblastoma (GBM) model 50 .…”
Section: Discussionmentioning
confidence: 95%
“…We observed that 4T1 TNBC cells undergo apoptosis when treated with iEFs in vitro. This finding is notable, especially in the context of bioelectricity, as other methods of applying electrical current or fields, such as tumor treating fields 47 (TTFs) and positive electrostatic charge therapy 48,49 (PECT), have also reported selective apoptosis of cancer cells. In addition, a recent study showed that TTFs enhance anti-tumor immune activation in a murine glioblastoma (GBM) model 50 .…”
Section: Discussionmentioning
confidence: 95%
“…Cytoplasmic degradation is predominant in Newcastle with liposomal doxorubicin‐treated malignant tissues; as the tissue matrix of the exposed tumours was not affected, the chance of necrosis was excluded (Figure 5I ). To demonstrate selective apoptosis in the tumour mass used IHC staining with P53 and Ki67 as markers of apoptosis and proliferative, respectively (Ozer et al., 2012 ; Zandi et al., 2021 ) (Figure 5II ). Also, H&E investigations of areas directly exposed to NDV as well as the body's vital organs, including the liver, kidneys, spleen, stomach, lungs, brain, and heart, were not demonstrated any pathological effects or any alternation, which indicates that the Newcastle virus will not negatively affect them (Figure 6I and II ).…”
Section: Resultsmentioning
confidence: 99%
“…Positive electrostatic fields showed no effect on cultured MCF‐7 cell lines, as we reported previously. [ 34,35 ] Cells were subjected to different concentrations of PTX (1 n m , 3 n m , 6 n m , 12 n m , 25 n m , 50 n m ) for periods of 24, 48, and 72 h. MTT analysis results showed that none of the 1 n m , 3 n m , or 6 n m treatments reached the IC 50 value for PTX after 72 h (Figure 2C). While neither positive electrostatic charge nor Paclitaxel could reduce the cell viability to 50%, the accumulation of DLNs caused by an applied external electrostatic field decreased cell viability to 45% after 24 h (Figure 2C).…”
Section: Resultsmentioning
confidence: 99%
“…Positive electrostatic fields showed no effect on cultured MCF-7 cell lines, as we reported previously. [34,35] Cells were subjected to different concentrations of PTX (1 nm, 3 nm, 6 nm, 12 nm, 25 nm, 50 nm) for periods of 24, 48, and 72 h. MTT analysis results showed that none of the 1 nm, 3 nm, or 6 nm treatments reached the IC 50 value for PTX after 72 h (Figure 2C).…”
Section: In Vitro Experimentsmentioning
confidence: 97%
See 1 more Smart Citation